Pervasive punishment: making sense of mass supervision - McNeill, Fergus (Emerald Publishing, 2019)
Despite its dramatic proliferation and diversification in recent decades, supervisory forms of punishment in the community (like probation, parole and unpaid work) have been largely invisible in scholarly and public discussion of criminal justice and its development in late-modern societies. The long-standing pre-occupation with the prison, and more recent concerns about 'mass incarceration' have allowed the emergence of 'mass supervision' to remain in the shadows. Pervasive Punishment insists that we remedy this neglect and exemplifies how we can do so. Drawing on thirty years of personal, practice and research experiences, it offers a compelling and rich account of the scale and social distribution of mass supervision, of the processes by which it has been legitimated, and of how it is experienced by those subject to it. Its innovative approach invites readers to look at, listen to and imagine punishment beyond the prison, through the use of innovative and creative methods including photography, song-writing and story-telling to explore and to represent 'mass supervision'. By so doing, this book offers new insights into how and why combining social science and creative practice can help develop a different kind of democratic dialogue about contentious social issues like crime and punishment. Though focused on the UK and the USA, the methods used in and analysis developed in this book will be of interest to scholars, students and practitioners elsewhere.